1996
DOI: 10.1089/hum.1996.7.17-2089
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Assessment of Human Hematopoietic Progenitor Cell Transduction in Long-Term Marrow Cultures

Abstract: Long-term marrow cultures (LTMCs) were established from 27 human marrows. Hematopoietic cells were subjected to multiple rounds of exposure to retroviral vectors during 3 weeks of culture. Seven different retroviral vectors were evaluated. LTMCs were assessed for viability, replication-competent retrovirus, progenitors capable of proliferating in immune-deficient mice, and gene transfer. The average number of adherent cells and committed granulocyte-macrophage progenitors (CFU-GM) recovered from LTMCs was 28% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Our preclinical studies of ex vivo gene transfer in Dexter-type LTMCs supported further clinical evaluation (Carter et al, 1992;Bienzle et al, 1994;Dubé et al, 1996;Stewart et al, 1996;Lutzko et al, 1999). These LTMCs are 1999.10:1953-1964. hem atopoietic microenvironm ents in which hematopoiesis may be maintained ex vivo for several weeks (Dexter et al, 1977).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our preclinical studies of ex vivo gene transfer in Dexter-type LTMCs supported further clinical evaluation (Carter et al, 1992;Bienzle et al, 1994;Dubé et al, 1996;Stewart et al, 1996;Lutzko et al, 1999). These LTMCs are 1999.10:1953-1964. hem atopoietic microenvironm ents in which hematopoiesis may be maintained ex vivo for several weeks (Dexter et al, 1977).…”
Section: Discussionsupporting
confidence: 64%
“…It was therefore postulated that appropriate manipulation of stromal-based culture systems might promote HSC activation into cell cycle (Cashm an et al, 1990;Bienzle et al, 1994) and, simultaneously, facilitate gene transfer into appropriate target cells. Preclinical studies indicated that multiple exposures of long-term, stroma-supporte d marrow cultures to retroviral vectors resulted in high-efficiency gene transfer into hem atopoietic progenitor cells with capacities for long-term in vivo proliferation (Carter et al, 1992;Bienzle et al, 1994;Dubé et al, 1996;Lutzko et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we used LTMC cells, which contain long-term culmre-initiating cells (LTC-IC). LTC-IC, which represent the most primitive progenitors detectable in vitro, can be transduced with retroviral vectors (Dube et al, 1996). Transduced LTC-IC are capable of reconstituting long-term hematopoiesis in large animals (Bienzle et al, 1994;Kiem et al, 1996).…”
Section: Analysis Of Transduction Efficiency Ofcd34~^ Cellsmentioning
confidence: 99%
“…Information demonstrating the presence of normal stem cells in the marproduction in short-and long-term hematopoietic cultures were significantly altered by the addition of MIP1-␣. Lack row of many CML patients [10][11][12]15,29 has become vital for the development of procedures which may allow for their of detectable MIP1-␣ growth inhibitory or stimulatory effects in our studies may be due to the concentration of differential manipulation. Various in vitro methodologies have been devised to purge leukemic marrow in order to MIP1-␣ used and to the frequency of its addition to the culture.…”
Section: Short-term Cultures Of Total Cd34 + Cells Patientsmentioning
confidence: 99%